TOTAL COLIFORM BACTERIA IN PIG FARM WASTE IN BADUNG DISTRICT OF BALI PROVINCE - Alegria, Cesarina Pascalia dos Santos; Suada, I Ketut; Agustina, Kadek Karang (Buletin Veteriner Udayana; Vol. 14 No. 6 December 2022, 2022)
Pig farm waste is residual waste from a pig farming activity such as urine, feces, feed residue and cage washing water. The purpose of this study was to determine the Total Coliform bacteria in pig farm waste in Badung District of Bali province. This research is an observational study, the location of the farm was chosen by purposive sampling. Sampling was carried out in four sub-districts, namely Petang sub-district, Abiansemal sub-district, Mengwi sub-district, and North Kuta sub-district. The volume of pig farm waste samples taken 500 ml of each farm then mixed into one per sub-district. The volume of pig farm waste samples taken 500 ml per farm. In each sub-district, has 3 three farmer waste then mixed into one sample per sub-district. In this study, the Coliform bacterial culture method used the spread method on Eosin Methelyne Blue Agar media. Positive samples are indicated by green metallic and pink colonies. The obtained data were analyze using One Way Anova. The results total Coliform are in Petang sub-district 175x10 8 CFU/mL, Abiansemal sub-district 142x10 8 CFU/mL, Megwi sub-district 114x10 8 CFU/mL and North Kuta sub-district 99x10 8 CFU/mL. Based on the results One Way Anova, it can be concluded the total number of Coliform bacteria in pig farm waste in Petang sub-district, Abiansemal sub-district, Mengwi sub-district and North Kuta sub-district was not significantly different (P>0,05). Pig farm waste with total Coliform bacteria that exceeds the standard limit needs to be treated first before being distributed to the environment.